Management strategies for the cloud revolution : how cloud computing is transforming business and why you can't afford to be left behind. - Babcock, Charles, ....- (New York : McGraw-Hill, 2010)
Increase efficiency while saving money with "on-demand" computing. The biggest game-changing force in business since the creation of the Internet, cloud computing simplifies and lowers the cost of operations while providing flexibility and power you never dreamed possible. Make your strategic move now, with Management Strategies for the Cloud Revolution! " Management Strategies for the Cloud Revolution is an important work that captures the concepts and technological advances fueling the rapid adoption of cloud computing today. It illuminates how specific core technologies have led to the emergence of those patterns as the foundation for the next generation of IT-managed infrastructure.
Inhoudsopgave : 1. The cloud revolution 2. The amorphous cloud 3. Virtualization changes everything 4. Just over the horizon, private clouds 5. The hybrid cloud 6. Overcoming resistance to the cloud 7. It reorganizes 8. Dangers abound: security in the cloud 9. Your cloud strategy: what kind of company do you want? 10. Calculating the future 11. Nebula: Nasa's strategic cloud
Keywords: Marketing -- Strategieën; Software